Impact of histone modifier-induced protection against autoimmune encephalomyelitis on multiple sclerosis treatment - Jayaraman, Sundararajan; Jayaraman, Arathi (Frontiers in Neurology, 2022)
Multiple sclerosis is a progressive demyelinating central nervous system disorder with unknown etiology. The condition has heterogeneous presentations, including relapsing-remitting multiple sclerosis and secondary and primary progressive multiple sclerosis. The genetic and epigenetic mechanisms underlying these various forms of multiple sclerosis remain elusive. Many disease-modifying therapies approved for multiple sclerosis are broad-spectrum immunomodulatory drugs that reduce relapses but do not halt the disease progression or neuroaxonal damage. Some are also associated with many severe side effects, including fatalities. Improvements in disease-modifying treatments, especially for primary progressive multiple sclerosis, remain an unmet need. Several experimental animal models are available to decipher the mechanisms involved in multiple sclerosis. These models help us to decipher the advantages and limitations of novel disease-modifying therapies for multiple sclerosis.